2022
DOI: 10.3390/pathogens11070801
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genomes of Theileria orientalis Chitose and Buffeli Genotypes Reveal within Species Translocations and Differences in ABC Transporter Content

Abstract: Theileria orientalis causes losses to cattle producers in Eastern Asia, Oceania and, more recently, North America. One pathogenic genotype (Ikeda) has been sequenced to the chromosomal level, while only draft genomes exist for globally distributed Chitose and Buffeli genotypes. To provide an accurate comparative gene-level analysis and help further understand their pathogenicity, we sequenced isolates of the Chitose and Buffeli genotypes of T. orientalis using long-read sequencing technology. A combination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Of these 11 genotypes, only Ikeda and chitose are known to be pathogenic and cause considerable production losses, morbidity, and/or mortality in Australia and New Zealand [15,16] Whole genome sequencing showed the genetic divergence of pathogenic Ikeda compared to less pathogenic Chitose and Buffeli genotypes, and proposed the genotype as a separate species [17]. A recent study in Australia revealed the existence of genetic differences between Chitose and Buffeli [18], further strengthening the above proposition.…”
Section: Classification Of T Orientalismentioning
confidence: 79%
“…Of these 11 genotypes, only Ikeda and chitose are known to be pathogenic and cause considerable production losses, morbidity, and/or mortality in Australia and New Zealand [15,16] Whole genome sequencing showed the genetic divergence of pathogenic Ikeda compared to less pathogenic Chitose and Buffeli genotypes, and proposed the genotype as a separate species [17]. A recent study in Australia revealed the existence of genetic differences between Chitose and Buffeli [18], further strengthening the above proposition.…”
Section: Classification Of T Orientalismentioning
confidence: 79%
“…A total of 1061 target proteins (95.3%) were identified that matched either the reference T. orientalis Shintoku genome or related apicomplexan parasites and other protozoans. This represents approximately one quarter of the total predicted proteome of T. orientalis with 4058, 3980 and 3924 genes predicted in the Ikeda, Chitose and Buffeli genomes respectively [ 22 , 23 ]. Approximately three quarters (78%; n = 829) of the proteins identified were aqueous phase proteins, while 22% ( n = 232) were from the detergent phase of the TX-114 extraction, representing membrane-associated and other hydrophobic proteins.…”
Section: Resultsmentioning
confidence: 99%
“…ToLocg 1 was also relatively abundant, although much less so (emPAI = 0.55) in the T. orientalis Buffeli aqueous phase. This protein was not identified in the Chitose genotype, and the gene encoding ToLocg 1 is absent from the Chitose genome [ 22 ]. Further investigation of the uncharacterised proteins revealed that the top 7 most abundant aqueous phase proteins in T. orientalis Ikeda (including ToLocg 1), belong to the same orthogroup as defined by Orthofinder [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy in results from these experimental transmission studies is best explained by variation in vector competence for the different genotypes of T. orientalis , given that the earlier studies were conducted with T. orientalis Buffeli. Indeed, differences in vector competence should be expected, given that T. orientalis genotypes are genetically distinct at the species level [ 65 ].…”
Section: Discussionmentioning
confidence: 99%